DFT calculation and infrared spectroscopic studies on free-base porphine and meso-substituted porphyrin - Arellano, Ian Harvey J. (Animo Repository, 2010)
Density functional theory (DFT) calculations have been extensively used to study the structures as well as the electronic and vibrational spectra of various compounds. Porphine and its derivatives are biologically and technologically important class of compounds which present interesting signatures in their spectra. We present here the infrared absorption spectrum of free-base 5,10,15,20-tetra-p-tolyl-21H, 23H-porphine. DFT calculations were performed to simulate the equilibrium geometry, energy levels, HOMO-LUMO gap, electrostatic potential map and the IR spectrum of the compound. Comparative analysis with meso-tetrakisphenylporphyrin was performed to evaluate the evolution of symmetry based properties as porphine is functionalized. A brief explanation of the origin of difficulty in the simulation of the properties of such large molecules was also provided.